Development of strong and ductile metastable face-centered cubic single-phase high-entropy alloys. (December 2019) - Wei, Daixiu; Li, Xiaoqing; Schönecker, Stephan; Jiang, Jing; Choi, Won-Mi; Lee, Byeong-Joo; Kim, Hyoung Seop; Chiba, Akihiko; Kato, Hidemi
Abstract: Face-centered cubic (fcc)-phase high-entropy alloys (HEAs) have attracted much academic interest, with the stacking fault energy (SFE) playing an important role in regulating their mechanical behaviors. Here, we revealed the principles for regulating both the elastic and plastic behaviors by composition modification and Mo addition in an fcc-phase quaternary CoCrFeNi system with the assistance of ab initio and thermodynamics calculations. An increase in Co content and a decrease in Fe and Ni contents reduced the fcc phase stability and SFE, but enhanced the elastic modulus, anisotropy, and lattice friction stress. A minor substitution of Co by Mo increased the lattice constant, but decreased the SFE and elastic modulus. Based on these findings, we developed a series of strong and ductile metastable fcc-phase Co x Cr25 (FeNi)70- x Mo5 ( x = 30, 40, 50) HEAs with mechanical properties superior to those of the CoCrFeNi HEAs. The careful investigation revealed that the enhanced mechanical properties are due to the Mo-addition-induced strengthening accompanied with a low-SFE-induced restriction of planar behavior of dislocations, mechanical twinning, and strain-induced martensitic transformation. The findings shed light on the development of high-performance HEAs. Graphical abstract: Image, graphical abstract